Study guides

☆☆

Q: 3p plus 7 equals 16 plus 2p?

Write your answer...

Submit

Still have questions?

Related questions

3p = 2p + 12subtracting 2p from both sidesp = 12 ■

3p = 2p + 12 subtract 2p from both sides 3p - 2p = 2p - 2p + 12 1p = 12 p = 12 this is how you solve this problem.

5p-1=2p-20 3p=21 p=7

8-3p-4 = 2p 4 - 3p = 2p add 3p to both sides 4 = 5p divide both sides by 5 4/5 = p

-5 + 3p - p = -5 + 2p

-2p+7.

-2p squared

2p - 9 = 5p + 12 subtract 2p fom both sides -9 = 3p +12 subtract 12 from both sides -21 = 3p divide both sides by 3 -7 = p

If you mean: 7p-3p+4-2 = 2p-1+10 => 4p+2 = 2p+9 => 2p = 7 Therefore: p = 7/2 => p = 3.5

6

It is an expression that can be simplified to: 3p+q

6

p = 5

Without prior knowledge of the value of q or r, it is impossible to calculate the answer to this equation.

3p + 4p +10 = 5p + 2 Subtracting 5p from both sides: 3p + 4p - 5p + 10 = 5p + 2 - 5p ie 2p + 10 = 2 Subtract 10 from both sides: 2p + 10 - 10 = 2 - 10 ie 2p = -8 Divide both sides by 2: p = -4

1s 2s 2p 2p 2p 3s 3p 3p 3p 4s 3d 3d 3d 3d 3d 4p

To find the value of p, simply use addition, subtraction and division to isolate p: 5p -1 = 2p + 20 5p - 2p - 1 = 2p - 2p + 20 3p - 1 + 1 = 20 + 1 3p/3 = 21/3 p = 7 The value of p is 7.

3p plus 7 equals 34, where P is equivalent to number 9.

If: 6p-2-3p = 16 Then: p = 6

4s>3p>3s>2p>1s.

3p2-2p-5 = (3p-5)(p+1) when factored

6p divide by 3p = 2

The expression can be simplified to: -8p--29

p is equal to any number greater than 12. 3p - 16 > 20 3p > 20 + 16 3p > 36 p > 12

3p+5+p = -23 3p+p = -23-5 4p = -28 p = -7